Endoscopic ablation of Barrett’s neoplasia with a new focal radiofrequency device: initial experience with the Halo60 - Allen, B.; Kapoor, N.; Willert, R.; McEwan, H.; Fullarton, G.; Penman, I. (Endoscopy, 2012)
Radiofrequency ablation (RFA) is an accepted treatment for the eradication of dysplastic Barrett’s esophagus (DBE) and residual Barrett’s esophagus after endoscopic resection of intramucosal adenocarcinoma. Circumferential balloon-based and focal catheter-based RFA devices are currently used (the Halo360 and Halo90). However, a new smaller focal ablation device (the Halo60) has been developed, which may be of benefit in patients with short tongues of Barrett’s neoplasia, small residual islands, difficult anatomy, or strictures. We report the first use of this device in 17 patients with either DBE or residual Barrett’s esophagus after endoscopic resection of intramucosal adenocarcinoma.